2022
DOI: 10.1061/(asce)me.1943-5479.0001074
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Dive into Worker Psychological Well-Being in the Construction Industry: A Systematic Review and Conceptual Framework

Abstract: The construction industry is stressful and worker psychological well-being (PWB) concerns are on the rise with high prevalence of mental health problems.However, there is currently no clear framework or system in the mainstream construction literature to guide management practices such as allocating resources, optimising work systems, and supporting worker well-being. In this study, a state-ofthe-art review was conducted on PWB constructs and the associated theoretical perspectives. This review of theories and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“…Intervention research should measure a range of mental health and wellbeing outcomes. Our review showed that studies applied limited measurement of mental health and mainly focussed on pathology-oriented concepts of mental health problems, such as burnout and distress, without detailing positive aspects of mental health and wellbeing and recognising the multi-dimensional nature of wellbeing recommended by a newly developed conceptual framework for construction interventions [ 55 ].Interventions focussed on strengthening the positive aspects of work (e.g. improving social support, enhancing influence at work) to pursue positive outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention research should measure a range of mental health and wellbeing outcomes. Our review showed that studies applied limited measurement of mental health and mainly focussed on pathology-oriented concepts of mental health problems, such as burnout and distress, without detailing positive aspects of mental health and wellbeing and recognising the multi-dimensional nature of wellbeing recommended by a newly developed conceptual framework for construction interventions [ 55 ].Interventions focussed on strengthening the positive aspects of work (e.g. improving social support, enhancing influence at work) to pursue positive outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Jones at al elaborated “An example of this is the well-intentioned focus on mental health in construction, which encourages workers to identify and seek help for their problems but does not commit organisations or the industry to taking action to reduce the risks inherent in the sector” [ 54 , p.546]. However, recently developed conceptual frameworks to guide practical management and research in construction integrate both individual-level and organisational-level approaches for the protection against workplace mental health risks and the promotion of wellbeing [ 55 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jones at al elaborated "An example of this is the well-intentioned focus on mental health in construction, which encourages workers to identify and seek help for their problems but does not commit organisations or the industry to taking action to reduce the risks inherent in the sector" [54, p.546]. However, recently developed conceptual frameworks to guide practical management and research in construction integrate both individual-level and organisational-level approaches for the protection against workplace mental health risks and the promotion of wellbeing [55][56][57].…”
Section: Workplace Mental Health Promotion In the Construction Sectormentioning
confidence: 99%
“…Based on the extensive literature review, various researchers concluded that many factors influence an individual’s risk tolerance capacity at the workplace [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. Some factors have a higher influence on an individual’s risk tolerance capacity, whereas others have a moderate, little to no impact, which ultimately influences the decision making of miners while dealing with the hazards at workplace [ [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ].…”
Section: Introductionmentioning
confidence: 99%